2017
DOI: 10.1080/1744666x.2018.1401469
|View full text |Cite
|
Sign up to set email alerts
|

Allergen immunotherapy in atopic dermatitis

Abstract: Atopic dermatitis (AD) is a chronic relapsing skin disease, characterized by flare-up due to the exposure to allergens in patients sensitized to them. Currently, therapy of AD is mainly based on symptomatic treatment and avoidance of irritating/allergenic factors, house dust mites being particularly important. Allergen immunotherapy (AIT) is suggested to be the only etiologic treatment, to modify the natural history of the disease. Areas covered: The aim of this review is investigating the putative role of AIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…While AD lesions were improved by HDM avoidance based on such measures [27,28], reductions in HDM levels had no effect on skin symptoms [29]. The effects of HDM allergen immunotherapy on AD lesions have been investigated by several groups [30,31]. Ridolo et al reported that the treatment of AD with the causative aeroallergen can be used as an add-on therapy in selected patients who are non-responsive to conventional therapy [30].…”
Section: House Dust Mites (Hdm)mentioning
confidence: 99%
See 2 more Smart Citations
“…While AD lesions were improved by HDM avoidance based on such measures [27,28], reductions in HDM levels had no effect on skin symptoms [29]. The effects of HDM allergen immunotherapy on AD lesions have been investigated by several groups [30,31]. Ridolo et al reported that the treatment of AD with the causative aeroallergen can be used as an add-on therapy in selected patients who are non-responsive to conventional therapy [30].…”
Section: House Dust Mites (Hdm)mentioning
confidence: 99%
“…The effects of HDM allergen immunotherapy on AD lesions have been investigated by several groups [30,31]. Ridolo et al reported that the treatment of AD with the causative aeroallergen can be used as an add-on therapy in selected patients who are non-responsive to conventional therapy [30].…”
Section: House Dust Mites (Hdm)mentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies suggest a positive effect for AE, there is conflicting evidence whether desensitization might influence AE in a positive way. 92 Ongoing and future efforts will need to determine which subgroups or endotypes of AE might benefit best. 93,94 Also in case of allergic contact dermatitis (ACD), evidence is conflictive regarding the impact on the course of AE.…”
Section: Are Allergies Relevant For the Pathogenesis Of Ae?mentioning
confidence: 99%
“…Allergen immunotherapy (AIT) is a treatment method whose effectiveness and reliability have been proven in cases where disease symptoms persist despite drug therapy and preventive care. It has been used as the most effective treatment since the early 1900s to cure allergic asthma (AA), allergic rhinitis (AR) and atopic dermatitis (AD) associated with respiratory system allergic sensitivity as well as anaphylaxis caused by venom (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%